A process for the detanning of chrome leather wastes utilising tannery effluents - Glaum, Deanne Melanie (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1994)
The considerable volume of chromium-bearing wastes generated during the process of leather tanning, exacerbated by the potential for trivalent chromium in the wastes to be oxidised to the toxic hexavalent state, has created a major waste disposal dilemma for the tanning industry. While methods are available for the safe and effective treatment of residual chrome-tanning liquors, little has been done to address the issue of the chrome-bearing solid wastes. Given the increasingly stringent environmental compliance standards facing tanneries, unless an appropriate treatment process is developed in the immediate future, the continued use of chromium as a tanning agent could be compromised. Recent investigations have demonstrated the potential of heated alkaline conditions for dechroming these solid wastes. This study expanded upon these considerations and examined the feasibility of utilising the highly alkaline tannery waste effluents as cost-effective, substitute alkaline media. The three effluents considered in this study, classed as lime sulphide liquors, were shown to be capable of dechroming wet blue shavings, with resultant separation of the solid wastes into a protein and a concentrated chromium product. The solubilised protein product contained low chromium concentrations which comply with legal discharge limits. The precipitated chromium product offers opportunity for reutilisation in the tannery. A novel industrial-scale treatment process, based on these investigations, indicated the process to be capable of treating the quantity of shavings produced on a daily basis by a medium to large scale tannery. Application of this method for the dechroming of other chrome-tanned solid wastes was also shown to be feasible.
Keywords: Tanneries -- Waste disposal; Recycling (Waste, etc.); Leather